Senescence during early differentiation reduced the chondrogenic differentiation capacity of mesenchymal progenitor cells - Voskamp, Chantal; Koevoet, Wendy J. L. M.; Van Osch, Gerjo J. V. M.; Narcisi, Roberto (Frontiers in Bioengineering and Biotechnology, 2023)
Mesenchymal stromal/progenitor cells (MSCs) are promising for cartilage cell-based therapies due to their chondrogenic differentiation capacity. However, MSCs can become senescent during in vitro expansion, a state characterized by stable cell cycle arrest, metabolic alterations, and substantial changes in the gene expression and secretory profile of the cell. In this study, we aimed to investigate how senescence and the senescence associated secretory phenotype (SASP) affect chondrogenic differentiation of MSCs. To study the effect of senescence, we exposed MSCs to gamma irradiation during expansion or during chondrogenic differentiation (pellet culture). When senescence was induced during expansion or at day-7 of chondrogenic differentiation, we observed a significant reduction in cartilage matrix. Interestingly, when senescence was induced at day-14 of differentiation, chondrogenesis was not significantly altered. Moreover, exposing chondrogenic pellets to medium conditioned by senescent pellets had no significant effect on the expression of anabolic or catabolic cartilage markers, suggesting a neglectable paracrine effect of senescence on cartilage generation in our model. Finally, we show that senescent MSCs had lower phosphorylated SMAD2 levels after TGFβ1stimulation compared to control MSCs. Overall, these results suggest that the occurrence of senescence in MSCs during expansion or early differentiation could be detrimental for cartilage tissue engineering.